Evaluasi Program Pemerintah Tentang Layak Anak di Kota Surabaya - Ismail; Bagus Ananda Kurniawan; Poppy Abellya Zalzabilla (Public Sphere Review, 2023)
This study aims to analyze the implementation of the government's child-friendly program in the city of Surabaya in making Child-Friendly Districts (KLA), supporting factors and inhibiting factors faced by the Surabaya City Government and the impact of the Government's program on child-friendly. The research method used is descriptive qualitative. The location of this research is at the Population Control, Women's Empowerment and Child Protection Office (DP5A) of Surabaya City and Three (3) sub-district areas that are pillars of the project (Genteng Sub-district Office, Wonocolo Sub-district, Benowo Sub-district), with the research subject being the Head of DP5A Surabaya City, Head of the People's Welfare and Economic Section in each sub-district area. The focus of this research is the Implementation of the Government's Child Friendly Program, the supporting and inhibiting factors faced by the Surabaya City Government and the impact of the Government's Child Friendly program. Sources of information were determined using purposive sampling techniques, data collection techniques through observation, interviews and documentation and data analysis techniques with data collection, data condensation, data presentation, and conclusion drawing. The results showed that: (1) Implementation of the Government Program on Child Friendly in Surabaya City. (2) The influencing factors are in accordance with the objectives of the activities that have been set. (3) The impact is that the cooperation that is established is quite effective, problem solving is fast, precise and straightforward, the achievement of activity results is enough to help the government in solving cases of child problems.